Heat-induced protein oxidation of soybean meal impairs growth performance and antioxidant status of broilers. (4th August 2018) - Lu, P; Xue, W Y; Zhang, X L; Wu, D W; Ding, L R; Wen, C; Zhou, Y M
ABSTRACT: This study aimed to evaluate the impact of oxidative modification on soybean meal (SBM ) proteins after exposure to different heating times, and the effects of the oxidized SBM on the growth performance [average daily feed intake (ADFI ), average daily gain (ADG ), and feed to gain ratio (F: G )], oxidative redox status [(reactive oxygen species (ROS ), total antioxidant capacity (TAC ), superoxide dismutase (SOD ), glutathione peroxidase (GSH -Px ), malondialdehyde (MDA ), and protein carbonyl (PC )]. A total of 400 one-day-old Arbor Acres chicks were randomly divided into 5 treatment groups with 8 replicates of 10 birds each. Birds in the control group (CON ) were fed diet containing non-heated SBM, and those in the treatment groups were fed SBM heated at 100°C for 1, 2, 4, and 8 h, for 42 d. Heated SBM (HSBM ) showed a relatively higher PC content in vitro . The ADG decreased, whereas the F:G increased linearly with an increase in heating time during the starter (days 1 to 21), grower (days 22 to 42), and the overall growth phases (days 1 to 42; P < 0.05). However, the ADFI decreased linearly only during the grower phase ( P < 0.05). The plasma, liver, and jejunum ROS levels, MDA concentrations, and PC contents increased linearly ( P < 0.05) in broilers fed HSBM. Furthermore, the TAC in the plasma and jejunum, and the total SOD and GSH- Px activities in the plasma, liver, and jejunum decreased linearly ( P < 0.05) in broilers when feeding HSBM. ( P < 0.05). The mRNA level of Nrf2 in the liver and jejunum was lower ( P < 0.05) in broilers fed diet containing the SBM after 8 h heat-treatment than in those fed the CON diet at days 42. This study suggested that heat-induced protein oxidation of SBM could decrease growth performance and impair antioxidant status of broilers.